The Impact of Emotional Intelligence, Social Values, Behavioral Control, Gender, and Financial Incentives on Pursuing a Career as a Public Accountant - Ulfa, Sinta Nuriya; Luh Gede Krisna Dewi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the influence of emotional intelligence, social values, behavioral control, gender, and financial rewards on students' aspirations for a career as a public accountant. The research was conducted among undergraduate students enrolled in the Accounting Study Program at the Faculty of Economics and Business, Udayana University, specifically from the Class of 2019. Data was collected using a structured questionnaire. The study employed a probability sampling method, specifically simple random sampling, resulting in a sample of 156 respondents. Multiple linear regression analysis was used to assess the relationships between the variables. The findings indicate that emotional intelligence, social values, and financial rewards positively influence students' desire to pursue a career as a public accountant, whereas behavioral control and gender do not have a significant effect.